Reinterpreting Problem-Based Learning in EFL Speaking Classrooms: Indonesian University Teachers’ Pedagogical Perspectives: English - Devi Purmayanti; Muh. Azhar Kholidi; Riandry Fadilah Nasution (JOEY: Journal of English Ibrahimy, 2026)
Problem-Based Learning (PBL) has gained prominence as a pedagogical approach for promoting learner autonomy, critical thinking, and communicative competence. However, little is known about how PBL is interpreted, adapted, and enacted by teachers in English as a Foreign Language (EFL) speaking classrooms, particularly in Indonesian higher education. This qualitative study examined Indonesian university EFL teachers’ perceptions and enactment of PBL in speaking instruction. Semi-structured interviews were conducted with five instructors from diverse institutional contexts and analyzed using thematic analysis. The findings show that teachers did not implement PBL as a fixed instructional model but reinterpreted it as a context-sensitive, fluency-oriented pedagogy shaped by learner readiness, classroom culture, and institutional constraints. While PBL was perceived to enhance student engagement, speaking confidence, and willingness to communicate, it was primarily adapted as discussion- and task-based activities rather than sustained inquiry cycles. These adaptations reveal how teacher cognition and local educational conditions mediate global pedagogical models. By foregrounding teachers situated enactment of PBL, this study extends existing PBL theory in EFL contexts and challenges assumptions that learner-centered pedagogies transfer seamlessly across settings. The study proposes a more context-responsive understanding of PBL for EFL speaking instruction and offers implications for teacher education, curriculum design, and institutional support in similarly constrained contexts.